The Effectiveness Of Synectics Strategy In Achievement And Statistical Thinking - et. al., Baidaa Mohammed Ahmed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to identify the effectiveness of Synectics strategy in the academic achevment sof the students of Mathematics department of Al-Mustansiria university, college of basic education and their statistical thinking . To achieve the aim of the research, the researchers use the experimental method, and designed two tests: one for achievement, and the other is for statistical thinking, each test consists of 20 MCQ items. After applying the two tests on the research sample which consisting of (82) students, distributed to two groups, experimental consisting of (42), and a control group consisting of (40) students, and statistical data processing, the results showed: the experimental group students generally outperformed, and female students over the control group students. In both tests, the differences between the average scores of male students were not statistically significant.